Progressive technologies of laser surfacing and gas‑thermal spraying - F. I. Panteleenko; Penchen Zheng (Литьë и металлургия)
The article notes the experience of Yantai Huaheng Energy Conservation Technology Co., Ltd in applying protective anti‑corrosion polymer coatings and discusses the most promising modern recovery and strengthening technologies of thermal spraying (PAPS, AS, HVAF, HVOF) and laser cladding (LASC). Examples of installations that the company has and typical restored machine parts with protective wearand corrosion‑resistant coatings and the microstructure of coatings are given. The main stages of a typical technological process for applying coatings are noted. Using the example of the company, the feasibility and effectiveness of the development of this area in China is noted.